Non-Governmental Organizations in Tijuana, Mexico Serving Deported Migrants from the United States - Altman, Claire; Chavez, Sergio; Lowrey, Kendal (Frontera Norte, 2021)
Non-Governmental Organizations (NGOs) are frequently an immigrant’s primary contact for support and service provision following deportation. We used semi-structured interviews and survey data collected in 2016 from the directors of 15 migrant-serving ONG in Tijuana, Mexico, to study how these Organizations support deportees. Building on the interdisciplinary nonprofit literature, we apply theories related to public values to frame our analysis. Our results suggest that NGOs in Tijuana contribute to public value across six roles while supporting deportees. As a pilot project, this paper provides a foundation for future studies of NGOs and the dynamics of U.S.-Mexico border cities receiving deportees.